Understanding the influence of parent-child conversations about dangers of drug use on cannabis use among high school students in Barbados - Sarah N. Oshi; Maria I. Espinoza-Hidrobo; Johanna L. Pozo-Neira; Sandra Cabrera-Arias (Journal of Education and Health Promotion)
BACKGROUND: Parent-child conversations are very important in influencing adolescent/youth behaviours. Objective of this study was to assess association between parent-child conversations on dangers of drug use and cannabis use among secondary school students in Barbados. MATERIALS AND METHOD: Data from the Barbados National School Survey (NSS) 2013 were analysed. Data were collected from a nationally representative sample of high school students drawn from 2nd to 6th forms across public and private secondary schools in Barbados in 2013. Descriptive analysis was done for sociodemographic characteristics and parent-child conversations. Multivariate logistic regression was done to assess the association between parent-child conversations on dangers of drug use and cannabis use among the subjects before and after adjusting for covariates. RESULTS: Parent-child conversations on dangers of drug use were significantly associated with past year cannabis use both before and after adjusting for covariates (crude odds ratio [COR] = 1.20, 95%CI: 1.04-1.38; adjusted odds ratio [AOR] adjusted odds ratio = 1.35, 95%CI: 1.15-1.58) but with students’ past month cannabis use only in the unadjusted logit model. Being 15-16 years, male, enrolled in 4th form, and belonging to widowed family structure was associated with reduced odds of past year and past month cannabis use. CONCLUSION: Significant positive association between parent-child conversations on the dangers of drug use with cannabis use is counter-intuitive and suggests that it is not just conversations but the type, content, and quality of conversations that matter in reducing students’ inclination to use cannabis.